2020
DOI: 10.9734/arrb/2020/v35i1230310
|View full text |Cite
|
Sign up to set email alerts
|

Biochar, Bentonite and Potassium Humate Effects on Saline Soil Properties and Nitrogen Loss

Abstract: Aim: In order to study the effect of biochar, bentonite and potassium humate on saline soil characteristics, barley growth and nitrogen loss, a column experiment was conducted. Addition of the above mention materials was hypothesized to improve the characteristics of saline soil and decrease nitrogen loss in the leachate solution. Place and Duration of Study: Farm of Soils and Water Department, Faculty of Agriculture, Al-Azhar University, Cairo, Egypt during the winter season of 2019. Methodology: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…The best treatment was 300 gm /tree K humate with magnetic water which decreased pH with about 40%. This result is in agreement with Fanous et al, (2017), Abdeen, (2020 and Mohamed and Sherif, (2020). This result cause by increase the effect of magnetic field K humate on organic matter in the soil.…”
Section: Soil Ph and Soil Cation Exchange Capacity (Cec)supporting
confidence: 93%
See 2 more Smart Citations
“…The best treatment was 300 gm /tree K humate with magnetic water which decreased pH with about 40%. This result is in agreement with Fanous et al, (2017), Abdeen, (2020 and Mohamed and Sherif, (2020). This result cause by increase the effect of magnetic field K humate on organic matter in the soil.…”
Section: Soil Ph and Soil Cation Exchange Capacity (Cec)supporting
confidence: 93%
“…Soil organic matter significantly increased by addition of potassium humate acts as organic matter which promote of soil. It is agreement with Abdeen (2020). Furthermore, the effect of magnetic water has effect to increase soil organic matter.…”
Section: Organic Matter and Soil Macronutrientssupporting
confidence: 87%
See 1 more Smart Citation
“…Many studies that used bentonite clay as a material for improving degraded soils, such as sandy and gypsum soils, indicated an increase in the growth, yield, and improvement of the quality of various crops, especially white and yellow corn, rice, beans, and barley, because the aim of improving soil characteristics is to increase the readiness of nutrients in it, raise its fertility, and use it in crop cultivation. To reduce its deterioration through the use of these improvers [47,48]. [49] reported their study on the role of bentonite in mitigating the harmful effects of drought stress in fenugreek (Trigonella foenum-graecum L. This study showed the morphological, physiological and biochemical responses of fenugreek under the influence of bentonite and water deficit.…”
Section: Bentonitementioning
confidence: 96%
“…To ameliorate saline-sodic soils, Li et al (2020) revealed that applying a mixture of microporous potassium-silicon-calcium mineral fertilizer and furfural residue improved K s , soil structure, and quality. Other studies (Abdeen, 2020;Ibrahim et al, 2019;Zhang et al, 2020) also showed that different biochar-amendment combinations (i.e., biochar-phosphorus fertilizer, biochar-bentonite-potassium humate, and biochar-gypsum) interacted and resulted in a reduction in BD, and an increment in K s , water retention, water availability, and aggregate stability in different soils.…”
Section: Introductionmentioning
confidence: 93%